Effects of Childhood Adversity on Bullying and Cruelty to Animals in the United States: Findings From a National Sample - Vaughn, Michael G. (2011)
This study examined effects of type of and cumulative burden of childhood adversities on bullying and cruelty to animals in the United States. Data were derived from Waves I and II of the National Epidemiologic Survey on Alcohol and Related Conditions, a nationally representative sample of U.S. adults. Structured psychiatric interviews were completed by trained lay interviewers between 2001–2002 and 2003–2004. Although the effects of childhood adversity diminished with the inclusion of confounding variables, several adversities remained significant. For bullying, these included being made to do chores that were too difficult or dangerous, threatening to hit or throw something, pushing, shoving, slapping, or hitting, and hitting that left bruises, marks, or injuries. With respect to cruelty to animals, swearing and saying hurtful things, having a parent or other adult living within the home that went to jail or prison, and adult/other person fondling/touching in a sexual way were significant. The final models indicated that the cumulative burden of childhood adversities had strong effects on the increased likelihood of bullying behavior but not cruelty to animals.